High-strength high-modulus carbon fiber and preparation method thereof
By controlling the electrostatic value and tow width ratio during the pre-oxidation process of carbon fiber, the problems of low carbon fiber strength and modulus and low interlayer shear strength of composite materials are solved, and the preparation of high-strength and high-layer shear strength of its composite materials are realized.
Patent Information
- Application Number
- CN202311348553.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-18
AI Technical Summary
In the prior art, carbon fiber has low strength and modulus, and the interlayer shear strength of composite materials is also low, which affects its application effect.
By reasonably controlling the ratio of the electrostatic value and tow width of the polyacrylonitrile-based raw filament during the preoxidation process, at least three temperature zones are set, and the ratio in the first temperature zone is 0.005-0.032V/mm, thereby reducing fiber surface wear and fine defects, improving the mechanical properties of carbon fibers and the interlayer shear strength of the composite material.
The preparation of high-strength and high-mode carbon fibers has been achieved. The tensile strength and modulus of carbon fibers have reached 3.98GPa and 526GPa, and the interlayer shear strength of the composite material has reached 55MPa, which has significantly improved its application performance.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon fiber preparation, and in particular to a high-strength and high-modulus carbon fiber and a preparation method thereof. Background Art
[0002] Carbon fiber is an inorganic high-performance fiber with a carbon content of more than 90%. It is a microcrystalline graphite material obtained by carbonizing and graphitizing organic fibers. It has the advantages of low density, high axial strength modulus, good fatigue resistance, fast electrical and thermal conductivity, good corrosion resistance, small thermal expansion coefficient, strong adaptability to sudden environmental changes, etc., and is widely used in various fields of the national economy. Carbon fiber not only has the inherent intrinsic properties of carbon materials, but also has the softness and processability of textile fibers. It is a new generation of high-performance fibers.
[0003] Carbon fiber has become an important strategic material for the development of national defense, military industry and national economy due to its excellent performance of high strength, high modulus and light weight. It not only has an irreplaceable position in military fields such as aerospace, but also shines in wind turbine blades, sports and leisure, pressure vessels, building protection, automobile transportation and other fields.
[0004] According to the performance differences, carbon fiber can be divided into general type and high performance type (including high strength type, high strength medium model, high strength high model, etc.). Carbon fiber can be divided into three types according to its raw materials: polyacrylonitrile based, asphalt based and viscose based. Among them, polyacrylonitrile based carbon fiber has become the main component of carbon fiber because of its easy raw material acquisition and excellent comprehensive mechanical properties of the fiber, accounting for more than 90% of the global carbon fiber production.
[0005] High-strength and high-modulus carbon fibers generally refer to high-performance carbon fibers with a modulus of more than 350 GPa and a tensile strength of more than 3.5 GPa. The preparation process of polyacrylonitrile-based carbon fibers includes three main processes: stock solution preparation, precursor preparation, and oxidation carbonization. The above three main processes each include multiple steps. The preparation process of high-strength and high-modulus carbon fibers is generally obtained by further high-temperature treatment (also known as graphitization) of the carbon fibers that have been subjected to high-temperature treatment. The carbon content of the high-strength and high-modulus carbon fibers after graphitization can reach more than 99%, and the elongation at break is significantly lower than that after graphitization, usually below 0.9%. The higher the modulus, the lower the elongation at break.
[0006] In the process of converting polyacrylonitrile fiber into carbon fiber, pre-oxidation is an important process that connects the past and the future, controlling the quality of carbon fiber and also controlling the output of carbon fiber. During the pre-oxidation process, polyacrylonitrile precursor undergoes a series of physical and chemical changes in hot air at 200-300°C, and its linear molecules are converted into heat-resistant trapezoidal structures. At the same time, friction will occur between the polyacrylonitrile fiber bundles and the drive, between the bundles, between the bundles and the hot air, and within / between the molecular chains inside the fiber, causing the fiber to accumulate a certain amount of static electricity, which in turn affects the fiber surface, mechanical properties and processing difficulty. Excessive static electricity causes greater wear on the fiber surface during the pre-oxidation process, destroying the morphology; too little static electricity is not conducive to the polarization effect during the surface treatment process.
[0007] Carbon fiber is rarely used directly. Most of them are processed into intermediate products or composite materials. This requires that carbon fiber must have strong bonding ability with other resin materials to meet the requirements of practical applications. Among them, interlaminar shear strength (ILSS) is an important basis for judging the bonding between carbon fiber and resin, which directly determines the strength and toughness of the composite material. It is defined as the strength limit under pure shear load, that is, the interlaminar shear stress when the specimen fails or the load reaches the maximum value. After carbonization treatment in a high-temperature furnace, the surface activity of carbon fiber itself decreases, and the bonding ability with the resin is weakened. At the same time, the ILSS of the composite material is also reduced, which will seriously affect the application effect. At present, the mainstream solution is to perform surface treatment on carbon fiber to improve the ILSS of the composite material. Electrochemical technology has attracted the attention of many researchers due to its convenient operation and significant effect, but the research content is limited to the influence of electrolyte type and process parameters on interface performance.
[0008] Patent application CN109161947A and patent application CN114086386A respectively improve the ILSS of high modulus carbon fiber composites by multi-stage anodizing treatment and parallel multi-stage electrolytic cells. Patent application CN112709064A uses multi-stage strong acid surface treatment to improve the surface activity of carbon fiber, thereby increasing its wettability with matrix resin to obtain a carbon fiber composite with higher ILSS. Chen Qiufei et al. (Effect of surface treatment process on ILSS and interface morphology of carbon fiber composites [J]. FRP / Composites, 2016(03):60-64+22.) explored the effect of different conductivity on the tensile strength of carbon fiber, ILSS of composite materials, and interface adhesion. The above patents and papers all improve the ILSS of carbon fiber composites by studying parameters such as the type of electrolyte, the number of electrolytic cells, and conductivity during the surface treatment process. The main influencing factors in the anodizing process mentioned in "Carbon Fiber and Graphite Fiber" (Chemical Industry Press, He Fu, September 2010, pages 303-311) include electrolyte, two-stage anodizing, electrolytic cell process, etc., and the influence of the aforementioned processing on the static electricity on the carbon fiber surface, which in turn affects its anodizing process, is also ignored. Summary of the invention
[0009] The purpose of the present invention is to overcome the problems of low strength and modulus of carbon fiber and low interlaminar shear strength of composite materials in the prior art, and to provide a high-strength and high-modulus carbon fiber and a preparation method thereof.
[0010] In order to achieve the above object, the present invention provides a method for preparing high-strength and high-modulus carbon fiber, the method comprising pre-oxidizing polyacrylonitrile-based precursor;
[0011] Wherein, the pre-oxidation treatment is provided with at least three temperature zones, and in the first temperature zone, the ratio of the electrostatic value of the polyacrylonitrile-based precursor yarn to the width of the polyacrylonitrile-based precursor yarn is 0.005-0.032 V / mm.
[0012] Preferably, during the pre-oxidation treatment in the first temperature zone, the bundle width of the polyacrylonitrile-based precursor is 0.0001-0.0008 times the number of single bundles of the polyacrylonitrile-based precursor, and the bundle width of the polyacrylonitrile-based precursor is measured in millimeters.
[0013] Preferably, in the first temperature zone, the electrostatic value y of the polyacrylonitrile-based precursor yarn satisfies the following formula:
[0014] -1.3x 3 +2.4x 2 -0.65x+0.03 <y<-3.4x 3 +6.5x 2 -0.12x+0.23;
[0015] The unit of y is V, and x represents the percentage of the pre-oxidation time in the first temperature zone to the total pre-oxidation time, and the value range of x is 25%-85%.
[0016] Preferably, during the pre-oxidation treatment, the width of the polyacrylonitrile-based precursor yarn is 4-80 mm.
[0017] Preferably, the number of strands in a single bundle of polyacrylonitrile-based precursor fibers is 1,000-320,000.
[0018] Preferably, the temperature of the first temperature zone is 200-270°C;
[0019] Preferably, the pre-oxidation residence time in the first temperature zone is 20-100 min;
[0020] Preferably, the stretching ratio in the first temperature zone is 1-1.1.
[0021] The polyacrylonitrile-based precursor is prepared by a wet spinning process;
[0022] Preferably, the fineness of the polyacrylonitrile-based precursor is 0.7-6 dtex.
[0023] Preferably, the method further comprises: subjecting the oxidized fibers obtained by pre-oxidation to low-temperature carbonization treatment, high-temperature carbonization treatment, graphitization treatment, electrochemical treatment, water washing, sizing and drying in sequence.
[0024] Preferably, the temperature of the low-temperature carbonization treatment is 400-800°C, and the total draft ratio is 0.95-1.08 times;
[0025] Preferably, the temperature of the high temperature carbonization treatment is 1200-1600°C, and the total draft ratio is 0.97-1.08 times;
[0026] Preferably, the temperature of the graphitization treatment is 2200-2800°C.
[0027] A second aspect of the present invention provides high-strength and high-modulus carbon fibers prepared by the method described above.
[0028] The method of the invention controls the static value of polyacrylonitrile-based precursor fibers during pre-oxidation to obtain high-strength and high-modulus carbon fibers, and the composite material has a relatively high interlaminar shear strength. DETAILED DESCRIPTION
[0029] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0030] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0031] In one aspect, the present invention provides a method for preparing high-strength and high-modulus carbon fiber, the method comprising pre-oxidizing polyacrylonitrile-based precursor;
[0032] Wherein, the pre-oxidation treatment is provided with at least three temperature zones, and in the first temperature zone, the ratio of the electrostatic value of the polyacrylonitrile-based precursor yarn to the width of the polyacrylonitrile-based precursor yarn is 0.005-0.032 V / mm.
[0033] In the method of the present invention, by reasonably controlling the ratio of the electrostatic value of the raw silk bundle to the width of the raw silk bundle during the pre-oxidation process in the first temperature zone, the surface wear of the fiber and the fine defects generated in this process are reduced, which is conducive to obtaining carbon fiber with higher strength. The weak electric field between the bundles can affect the physical and chemical reactions during the pre-oxidation process. The appropriate electrostatic value can slow down the oxidation process and the formation of the skin-core structure, which is conducive to improving the mechanical properties of the carbon fiber. At the same time, appropriate static electricity can polarize the surface of the carbon fiber and improve the interlaminar shear strength of its composite material.
[0034] In a specific embodiment, in the first temperature zone, the ratio of the electrostatic value of the polyacrylonitrile-based precursor yarn to the width of the polyacrylonitrile-based precursor yarn can be 0.005V / mm, 0.006V / mm, 0.007V / mm, 0.008V / mm, 0.009V / mm, 0.01V / mm, 0.012V / mm, 0.015V / mm, 0.016V / mm, 0.018V / mm, 0.02V / mm, 0.022V / mm, 0.025V / mm, 0.026V / mm, 0.028V / mm, 0.03V / mm or 0.032V / mm.
[0035] In order to further improve the mechanical properties of carbon fiber and the interlaminar shear strength of the composite material, in a preferred embodiment, during the pre-oxidation treatment in the first temperature zone, the bundle width of the polyacrylonitrile-based precursor is 0.0001-0.0008 times the number of single bundles of the polyacrylonitrile-based precursor, and the bundle width of the polyacrylonitrile-based precursor is measured in millimeters; specifically, the bundle width of the polyacrylonitrile-based precursor can be 0.0001 times, 0.0002 times, 0.0003 times, 0.0004 times, 0.0005 times, 0.0006 times, 0.0007 times or 0.0008 times the number of single bundles of fibers.
[0036] In order to further improve the mechanical properties of carbon fiber and the interlaminar shear strength of the composite material, in a preferred embodiment, in the first temperature zone, the electrostatic value y of the fiber bundle is controlled during the pre-oxidation process to satisfy the following formula:
[0037] -1.3x 3 +2.4x 2 -0.65x+0.03 <y<-3.4x 3 +6.5x 2 -0.12x+0.23;
[0038] Among them, the unit of y is V, x represents the percentage of the pre-oxidation time in the first temperature zone to the total pre-oxidation time, and the value range of x is 25%-85%; specifically, x can be 25%, 30%, 40%, 45%, 50%, 65%, 75% or 80%.
[0039] In a preferred embodiment, during the pre-oxidation treatment, the width of the polyacrylonitrile-based precursor yarn is controlled to be 4-80 mm; specifically, it can be 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm, 45 mm, 50 mm, 55 mm, 60 mm, 65 mm, 70 mm or 80 mm.
[0040] In a preferred embodiment, during the pre-oxidation treatment process, the number of single bundles of polyacrylonitrile-based precursor fibers is controlled to be 1000-320000; specifically, it can be 1000, 2000, 3000, 4000, 5000, 8000, 10000, 12000, 20000, 240000, 40000, 48000, 50000, 60000, 70000, 80000, 96000, 100000, 120000, 200000, 300000 or 320000.
[0041] In a preferred embodiment, the temperature of the pre-oxidation treatment is 200-300° C., and the total residence time ranges from 100 to 140 min; specifically, it can be 100 min, 120 min or 140 min.
[0042] In a preferred embodiment, the pre-oxidation treatment is performed in an air atmosphere.
[0043] In a preferred embodiment, the temperature of the pre-oxidation treatment in the first temperature zone is controlled to be 200-270°C; specifically, it can be 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C or 270°C.
[0044] In a preferred embodiment, the pre-oxidation residence time in the first temperature zone is 20-100 min; specifically, it can be 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 60 min, 70 min, 80 min, 90 min or 100 min.
[0045] In a preferred embodiment, the drawing ratio of the polyacrylonitrile precursor during the pre-oxidation treatment in the first temperature zone is 1-1.1.
[0046] In a specific embodiment, the pre-oxidation is set in three temperature zones, the pre-oxidation treatment temperature in the first temperature zone is 200-270°C; the pre-oxidation treatment temperature in the second temperature zone is 220-280°C; the pre-oxidation treatment temperature in the third temperature zone is 240-300°C; and the temperatures of the three temperature zones are set in increments.
[0047] In the method of the present invention, the polyacrylonitrile-based precursor may be a polyacrylonitrile-based precursor conventionally used in the art for preparing carbon fiber. In a preferred embodiment, the polyacrylonitrile-based precursor is prepared by a wet spinning process.
[0048] Further preferably, the fineness of the polyacrylonitrile-based precursor is 0.7-6 dtex; specifically, it can be 0.7 dtex, 0.8 dtex, 0.83 dtex, 0.95 dtex, 1 dtex, 2 dtex, 3 dtex, 4 dtex, 5 dtex or 6 dtex.
[0049] Preferably, the method for preparing high-strength and high-modulus carbon fibers further comprises: subjecting the oxidized fibers obtained by pre-oxidation to low-temperature carbonization treatment, high-temperature carbonization treatment, graphitization treatment, electrochemical treatment, water washing, sizing and drying in sequence.
[0050] Further preferably, the temperature of the low-temperature carbonization treatment is 400-800° C., and the total drawing ratio is 0.95-1.08 times.
[0051] Further preferably, the temperature of the high temperature carbonization treatment is 1200-1600° C., and the total drawing ratio is 0.97-1.08 times.
[0052] Further preferably, the temperature of the graphitization treatment is 2200-2800°C.
[0053] In the present invention, in the first temperature zone, the test method for the electrostatic value of the polyacrylonitrile-based precursor yarn bundle is: measured by a Keyence SK series handheld electrostatic detector, the measuring position is 5 cm from the outlet of the pre-oxidation furnace, and the detection spot is located in the center of the fiber bundle.
[0054] The second aspect of the present invention provides high-strength and high-modulus carbon fibers prepared by the method described above, wherein the high-strength and high-modulus carbon fibers have a tensile strength of ≥3.98 GPa, a tensile modulus of ≥526 GPa, and an interlaminar shear strength of the composite material of ≥55 MPa.
[0055] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.
[0056] The polyacrylonitrile precursor used in the following examples and comparative examples is prepared according to the following method: the spinning solution is accurately measured by a metering pump, filtered again, and then a wet spinning method is used; subsequently, two-stage coagulation and drawing, four-stage hot water drawing, water washing, oiling, drying and densification, steam drawing and steam heat setting are carried out in sequence, and finally the carbon fiber precursor is obtained by collecting. Among them, the drawing ratios of the two-stage coagulation and drawing are 1.05 and 1.15 respectively; the four-stage hot water drawing is carried out in hot water at 80-95°C, and the total drawing ratio is 3.5 times; the washing process is carried out at 75°C, and no drawing is done during the process; the drying and densification adopts a five-temperature zone gradient heating method, which are 90°C, 105°C, 120°C, 130°C, and 135°C respectively; the steam drawing pressure is 0.55MPa, and the drawing ratio is 3.25 times; the temperature of steam heat setting is 105°C.
[0057] The fineness test of polyacrylonitrile-based raw yarn refers to the method recorded in the national standard GB / T 14343.
[0058] The mechanical properties test of carbon fiber refers to the method recorded in the national standard GB / T 3362-2017, and the interlaminar shear strength test of carbon fiber composite materials refers to the short beam method recorded in the standard ISO 14130.
[0059] Example 1
[0060] The polyacrylonitrile-based precursor fiber bundle (self-made, with a single bundle number of 12000 and a fineness of 0.83dtex) is sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling and drying, and finally the fiber is collected to obtain high-strength and high-modulus carbon fiber; wherein the pre-oxidation process is carried out in an air atmosphere, and passes through three temperature zones in sequence, the pre-oxidation temperature in the first temperature zone is 220°C, the residence time is 30min, the pre-oxidation time in the first temperature zone accounts for a percentage x=25% of the total pre-oxidation time, the drafting ratio of the polyacrylonitrile precursor fiber in the first temperature zone pre-oxidation treatment process is 1.0, the pre-oxidation temperature in the second temperature zone is 235°C, the residence time is 60min, the pre-oxidation temperature in the third temperature zone is 250°C, the residence time is 30min, and the total residence time is 120min; in the pre-oxidation process in the first temperature zone, the width of the polyacrylonitrile-based precursor fiber bundle is controlled to be 5mm, the electrostatic value y of the polyacrylonitrile-based precursor fiber bundle is 0.05, the unit is V, and y and x satisfy the following relationship: -1.3x 3+2.4x 2 -0.65x+0.03 <y<-3.4x 3 +6.5x 2 -0.12x+0.23; the low-temperature carbonization process is carried out at 400°C in the presence of inert gas, with a total draw ratio of 1.05 times; the high-temperature carbonization process is carried out at 1200°C in the presence of inert gas, with a total draw ratio of 1.06 times; the graphitization process is carried out at 2200°C in the presence of inert gas; the surface treatment adopts the electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 2%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The obtained carbon fiber has a tensile strength of 4.05GPa, a tensile modulus of 540GPa, and an interlaminar shear strength of the carbon fiber composite material of 55Mpa.
[0061] Example 2
[0062] The polyacrylonitrile-based precursor fiber bundle (self-made, with a single bundle number of 24,000 and a fineness of 0.95 dtex) is sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling, drying, and finally the fiber is collected to obtain high-strength and high-modulus carbon fiber. Among them, the pre-oxidation process is carried out in an air atmosphere, and passes through three temperature zones in sequence. The pre-oxidation temperature in the first temperature zone is 200°C, the residence time is 60min, and the pre-oxidation time in the first temperature zone accounts for a percentage of x=50% of the total pre-oxidation time. During the pre-oxidation treatment in the first temperature zone, the drafting ratio of the polyacrylonitrile precursor fiber is 1.08, the pre-oxidation temperature in the second temperature zone is 220°C, the residence time is 20min, the pre-oxidation temperature in the third temperature zone is 245°C, the residence time is 40min, and the total residence time is 120min; during the pre-oxidation process in the first temperature zone, the width of the polyacrylonitrile-based precursor fiber bundle is controlled to be 9mm, and the electrostatic value of the polyacrylonitrile-based precursor fiber bundle is y=0.2, the unit is V, and y and x satisfy the following relationship: -1.3x 3 +2.4x 2 -0.65x+0.03 <y<-3.4x 3 +6.5x 2 -0.12x+0.23; low temperature carbonization process is carried out at 550℃ in the presence of inert gas, with a total draw ratio of 1.07 times; high temperature carbonization process is carried out at 1250℃ in the presence of inert gas, with a total draw ratio of 1.04 times; graphitization process is carried out at 2350℃ in the presence of inert gas; surface treatment adopts electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 1.8%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The obtained carbon fiber tensile strength is 4.12GPa, the tensile modulus is 547GPa, and the interlaminar shear strength of the carbon fiber composite material is 55.7Mpa.
[0063] Example 3
[0064] The polyacrylonitrile-based precursor fiber bundle (self-made, with a single bundle number of 48,000 and a fineness of 0.86 dtex) is sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling, drying, and finally the fiber is collected to obtain high-strength and high-modulus carbon fiber. Among them, the pre-oxidation process is carried out in an air atmosphere, and passes through three temperature zones in sequence. The pre-oxidation temperature in the first temperature zone is 215°C, the residence time is 36 minutes, and the pre-oxidation time in the first temperature zone accounts for a percentage of x=30% of the total pre-oxidation time. During the pre-oxidation treatment in the first temperature zone, the drafting ratio of the polyacrylonitrile precursor fiber is 1.06, the pre-oxidation temperature in the second temperature zone is 220°C, the residence time is 60 minutes, the pre-oxidation temperature in the third temperature zone is 230°C, the residence time is 24 minutes, and the total residence time is 120 minutes; during the pre-oxidation process in the first temperature zone, the width of the polyacrylonitrile-based precursor fiber bundle is controlled to be 37 mm, and the electrostatic value of the polyacrylonitrile-based precursor fiber bundle is y=0.5, the unit is V, and y and x satisfy the following relationship: -1.3x 3 +2.4x 2 -0.65x+0.03 <y<-3.4x 3 +6.5x 2 -0.12x+0.23; the low-temperature carbonization process is carried out at 650°C in the presence of inert gas, with a total draw ratio of 1.08 times; the high-temperature carbonization process is carried out at 1400°C in the presence of inert gas, with a total draw ratio of 1.03 times; the graphitization process is carried out at 2500°C in the presence of inert gas; the surface treatment adopts the electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 2.4%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The obtained carbon fiber has a tensile strength of 4.18GPa, a tensile modulus of 534GPa, and an interlaminar shear strength of the carbon fiber composite material of 58.8Mpa.
[0065] Example 4
[0066] The polyacrylonitrile-based raw fiber bundle (self-made, with 96,000 fibers in a single bundle and a fineness of 2.76 dtex) was sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling, and drying, and finally collected to obtain high-strength and high-modulus carbon fiber. Among them, the pre-oxidation process is carried out in an air atmosphere, passing through three temperature zones in sequence, the pre-oxidation temperature of the first temperature zone is 210°C, the residence time is 60min, the pre-oxidation time of the first temperature zone accounts for x=50% of the total pre-oxidation time, the drafting ratio of the polyacrylonitrile precursor during the pre-oxidation treatment in the first temperature zone is 1.05, the pre-oxidation temperature of the second temperature zone is 225°C, the residence time is 30min, the pre-oxidation temperature of the third temperature zone is 240°C, the residence time is 30min, and the total residence time is 120min; during the pre-oxidation process in the first temperature zone, the width of the polyacrylonitrile-based precursor bundle is controlled to be 68mm, and the electrostatic value of the polyacrylonitrile-based precursor bundle is y=1.5, the unit is V, and y and x satisfy the following relationship: -1.3x 3 +2.4x 2 -0.65x+0.03 <y<-3.4x 3 +6.5x 2 -0.12x+0.23; the low-temperature carbonization process is carried out at 800°C in the presence of inert gas, with a total draw ratio of 1.08 times; the high-temperature carbonization process is carried out at 1550°C in the presence of inert gas, with a total draw ratio of 1.04 times; the graphitization process is carried out at 2750°C in the presence of inert gas; the surface treatment adopts the electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 1.8%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The obtained carbon fiber has a tensile strength of 4.17GPa, a tensile modulus of 537GPa, and an interlaminar shear strength of the carbon fiber composite material of 59.6Mpa.
[0067] Example 5
[0068] The polyacrylonitrile-based raw fiber bundle (self-made, with 320,000 fibers in a single bundle and a fineness of 5.77 dtex) was sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling, and drying, and finally collected to obtain high-strength and high-modulus carbon fiber. The pre-oxidation process is carried out in an air atmosphere and passes through three temperature zones in sequence. The pre-oxidation temperature in the first temperature zone is 215°C and the residence time is 96 minutes. The pre-oxidation time in the first temperature zone accounts for x=80% of the total pre-oxidation time. The drafting ratio of the polyacrylonitrile precursor in the pre-oxidation treatment process in the first temperature zone is 1.1. The pre-oxidation temperature in the second temperature zone is 235°C and the residence time is 12 minutes. The pre-oxidation temperature in the third temperature zone is 240°C and the residence time is 12 minutes. The total residence time is 120 minutes. During the pre-oxidation process in the first temperature zone, the width of the polyacrylonitrile-based precursor bundle is controlled to be 80 mm, and the electrostatic value of the polyacrylonitrile-based precursor bundle is y=2.5, the unit is V, and y and x satisfy the following relationship: -1.3x 3 +2.4x 2 -0.65x+0.03 <y<-3.4x 3 +6.5x 2 -0.12x+0.23; the low-temperature carbonization process is carried out at 750°C in the presence of inert gas, with a total draw ratio of 1.05 times; the high-temperature carbonization process is carried out at 1800°C in the presence of inert gas, with a total draw ratio of 1.06 times; the graphitization process is carried out at 2800°C in the presence of inert gas; the surface treatment adopts the electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 2%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The obtained carbon fiber has a tensile strength of 3.98GPa, a tensile modulus of 534GPa, and an interlaminar shear strength of the carbon fiber composite material of 60.5Mpa.
[0069] Example 6
[0070] The polyacrylonitrile-based raw fiber bundle (self-made, with 48,000 fibers in a single bundle and a fineness of 1.87 dtex) was sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling, and drying, and finally collected to obtain high-strength and high-modulus carbon fiber. The pre-oxidation process is carried out in an air atmosphere and passes through three temperature zones in sequence. The pre-oxidation temperature in the first temperature zone is 215°C and the residence time is 30 minutes. The pre-oxidation time in the first temperature zone accounts for x=25% of the total pre-oxidation time. The drafting ratio of the polyacrylonitrile precursor during the pre-oxidation treatment in the first temperature zone is 1.08. The pre-oxidation temperature in the second temperature zone is 235°C and the residence time is 45 minutes. The pre-oxidation temperature in the third temperature zone is 250°C and the residence time is 45 minutes. The total residence time is 120 minutes. During the pre-oxidation process in the first temperature zone, the width of the polyacrylonitrile-based precursor bundle is controlled to be 37 mm, and the electrostatic value of the polyacrylonitrile-based precursor bundle is y=0.6, the unit is V, and y and x satisfy the following relationship: -1.3x 3 +2.4x 2 -0.65x+0.03 <y<-3.4x 3 +6.5x 2 -0.12x+0.23; the low-temperature carbonization process is carried out at 700°C in the presence of inert gas, with a total draw ratio of 1.05 times; the high-temperature carbonization process is carried out at 1450°C in the presence of inert gas, with a total draw ratio of 1.06 times; the graphitization process is carried out at 2650°C in the presence of inert gas; the surface treatment adopts the electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 2%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The obtained carbon fiber has a tensile strength of 4.04GPa, a tensile modulus of 539GPa, and an interlaminar shear strength of the carbon fiber composite material of 62.2Mpa.
[0071] Example 7
[0072] The polyacrylonitrile-based precursor fiber bundle (self-made, with a single bundle number of 96,000 and a fineness of 2.94 dtex) is sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling, drying, and finally the fiber is collected to obtain high-strength and high-modulus carbon fiber. Among them, the pre-oxidation process is carried out in an air atmosphere, and passes through three temperature zones in sequence. The pre-oxidation temperature in the first temperature zone is 210°C and the residence time is 60min. The pre-oxidation time in the first temperature zone accounts for a percentage of x=50% of the total pre-oxidation time. During the pre-oxidation treatment in the first temperature zone, the drafting ratio of the polyacrylonitrile precursor fiber is 1.06, the pre-oxidation temperature in the second temperature zone is 230°C and the residence time is 20min, the pre-oxidation temperature in the third temperature zone is 250°C and the residence time is 40min, and the total residence time is 120min; during the pre-oxidation process in the first temperature zone, the width of the polyacrylonitrile-based precursor fiber bundle is controlled to be 76mm, and the electrostatic value of the polyacrylonitrile-based precursor fiber bundle is y=1.2, the unit is V, and y and x satisfy the following relationship: -1.3x 3 +2.4x 2 -0.65x+0.03 <y<-3.4x 3 +6.5x 2 -0.12x+0.23; low temperature carbonization process is carried out at 750℃ in the presence of inert gas, with a total draw ratio of 1.05 times; high temperature carbonization process is carried out at 1650℃ in the presence of inert gas, with a total draw ratio of 1.06 times; graphitization process is carried out at 2750℃ in the presence of inert gas; surface treatment adopts electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 2%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The obtained carbon fiber tensile strength is 4.02GPa, the tensile modulus is 526GPa, and the interlaminar shear strength of the carbon fiber composite material is 61.1Mpa.
[0073] Example 8
[0074] The polyacrylonitrile-based raw fiber bundle (self-made, with 200,000 fibers in a single bundle and a fineness of 4.87 dtex) was sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling, and drying, and finally the high-strength and high-modulus carbon fiber was obtained by spinning. The pre-oxidation process is carried out in an air atmosphere and passes through three temperature zones in sequence. The pre-oxidation temperature in the first temperature zone is 210°C and the residence time is 42 minutes. The pre-oxidation time in the first temperature zone accounts for a percentage of x=35% of the total pre-oxidation time. During the pre-oxidation treatment in the first temperature zone, the drafting ratio of the polyacrylonitrile precursor is 1.08. The pre-oxidation temperature in the second temperature zone is 215°C and the residence time is 40 minutes. The pre-oxidation temperature in the third temperature zone is 220°C and the residence time is 38 minutes. The total residence time is 120 minutes. During the pre-oxidation in the first temperature zone, the width of the polyacrylonitrile-based precursor bundle is controlled to be 78 mm, and the electrostatic value of the polyacrylonitrile-based precursor bundle is y=0.768, with a unit of V, and y and x satisfy the following relationship: -1.3x 3 +2.4x 2 -0.65x+0.03 <y<-3.4x 3 +6.5x 2 -0.12x+0.23; the low-temperature carbonization process is carried out at 800°C in the presence of inert gas, with a total draw ratio of 1.05 times; the high-temperature carbonization process is carried out at 1550°C in the presence of inert gas, with a total draw ratio of 1.0 times; the graphitization process is carried out at 2500°C in the presence of inert gas; the surface treatment adopts the electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 2%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The obtained carbon fiber has a tensile strength of 4.04GPa, a tensile modulus of 538GPa, and an interlaminar shear strength of the carbon fiber composite material of 64.7Mpa.
[0075] Example 9
[0076] The polyacrylonitrile-based raw fiber bundle (self-made, with 60,000 fibers in a single bundle and a fineness of 2.74 dtex) was sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling, and drying, and finally collected to obtain high-strength and high-modulus carbon fiber. The pre-oxidation process is carried out in an air atmosphere and passes through three temperature zones in sequence. The pre-oxidation temperature in the first temperature zone is 200°C and the residence time is 36 minutes. The pre-oxidation time in the first temperature zone accounts for a percentage of x=30% of the total pre-oxidation time. During the pre-oxidation treatment in the first temperature zone, the drafting ratio of the polyacrylonitrile precursor is 1.04. The pre-oxidation temperature in the second temperature zone is 225°C and the residence time is 42 minutes. The pre-oxidation temperature in the third temperature zone is 250°C and the residence time is 42 minutes. The total residence time is 120 minutes. During the pre-oxidation in the first temperature zone, the width of the polyacrylonitrile-based precursor bundle is controlled to be 68 mm, and the electrostatic value of the polyacrylonitrile-based precursor bundle is y=0.837, with a unit of V, and y and x satisfy the following relationship: -1.3x 3 +2.4x 2 -0.65x+0.03 <y<-3.4x 3 +6.5x 2 -0.12x+0.23; the low-temperature carbonization process is carried out at 700°C in the presence of inert gas, with a total draw ratio of 1.05 times; the high-temperature carbonization process is carried out at 1200°C in the presence of inert gas, with a total draw ratio of 1.06 times; the graphitization process is carried out at 2200°C in the presence of inert gas; the surface treatment adopts the electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 2%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The tensile strength of the obtained carbon fiber is 4.03GPa, the tensile modulus is 541GPa, and the interlaminar shear strength of the carbon fiber composite material is 65.2Mpa.
[0077] Example 10
[0078] The polyacrylonitrile-based raw fiber bundle (self-made, with 48,000 fibers in a single bundle and a fineness of 1.86 dtex) was sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling, and drying, and finally the high-strength and high-modulus carbon fiber was obtained by spinning. The pre-oxidation process is carried out in an air atmosphere and passes through three temperature zones in sequence. The pre-oxidation temperature in the first temperature zone is 210°C and the residence time is 30 minutes. The pre-oxidation time in the first temperature zone accounts for a percentage of x=25% of the total pre-oxidation time. During the pre-oxidation treatment in the first temperature zone, the drafting ratio of the polyacrylonitrile precursor is 1.1. The pre-oxidation temperature in the second temperature zone is 235°C and the residence time is 35 minutes. The pre-oxidation temperature in the third temperature zone is 240°C and the residence time is 65 minutes. The total residence time is 120 minutes. During the pre-oxidation in the first temperature zone, the width of the polyacrylonitrile-based precursor bundle is controlled to be 16 mm, and the electrostatic value of the polyacrylonitrile-based precursor bundle is y=0.243, the unit is V, and y and x satisfy the following relationship: -1.3x 3 +2.4x 2 -0.65x+0.03 <y<-3.4x 3 +6.5x 2 -0.12x+0.23; the low-temperature carbonization process is carried out at 650°C in the presence of inert gas, with a total draw ratio of 1.05 times; the high-temperature carbonization process is carried out at 1400°C in the presence of inert gas, with a total draw ratio of 1.06 times; the graphitization process is carried out at 2200°C in the presence of inert gas; the surface treatment adopts the electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 2%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The tensile strength of the obtained carbon fiber is 4.04GPa, the tensile modulus is 551GPa, and the interlaminar shear strength of the carbon fiber composite material is 62.4Mpa.
[0079] Comparative Example 1
[0080] The polyacrylonitrile-based precursor filament bundle (self-made, with 6000 strands in a single bundle and a fineness of 0.80dtex) is sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling, drying, and finally the high-strength and high-modulus carbon fiber is obtained. The pre-oxidation process is carried out in an air atmosphere and passes through three temperature zones in sequence. The pre-oxidation temperature in the first temperature zone is 220°C and the residence time is 30min. The pre-oxidation time in the first temperature zone accounts for x=25% of the total pre-oxidation time. During the pre-oxidation treatment in the first temperature zone, the drafting ratio of the polyacrylonitrile precursor is 1.08. The pre-oxidation temperature in the second temperature zone is 235°C and the residence time is 35min. The pre-oxidation temperature in the third temperature zone is 250°C and the residence time is 55min. The total residence time is 120min. During the oxidation process, the width of the polyacrylonitrile-based precursor fiber bundle is controlled to be 10mm, and the electrostatic value of the polyacrylonitrile-based precursor fiber bundle is y=0.006, with the unit of V; the low-temperature carbonization process is carried out at 400°C in the presence of inert gas; the high-temperature carbonization process is carried out at 1200°C in the presence of inert gas, with a total draft ratio of 1.06 times; the graphitization process is carried out at 2200°C in the presence of inert gas; the surface treatment adopts the electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 2%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The obtained carbon fiber has a tensile strength of 3.84GPa, a tensile modulus of 476GPa, and an interlaminar shear strength of the carbon fiber composite material of 42Mpa.
[0081] Comparative Example 2
[0082] The polyacrylonitrile-based precursor filament bundle (self-made, with 80,000 strands in a single bundle and a fineness of 1.75 dtex) is sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling, drying, and finally the high-strength and high-modulus carbon fiber is obtained. The pre-oxidation process is carried out in an air atmosphere and passes through three temperature zones in sequence. The pre-oxidation temperature in the first temperature zone is 200°C and the residence time is 48 minutes. The pre-oxidation time in the first temperature zone accounts for a percentage of x=40% of the total pre-oxidation time. During the pre-oxidation treatment in the first temperature zone, the drafting ratio of the polyacrylonitrile precursor is 1.05. The pre-oxidation temperature in the second temperature zone is 215°C and the residence time is 36 minutes. The pre-oxidation temperature in the third temperature zone is 220°C and the residence time is 36 minutes. The total residence time is 120 minutes. During the pre-oxidation process in the first temperature zone, the pre-oxidation temperature is 215°C and the residence time is 36 minutes. The pre-oxidation temperature in the third temperature zone is 220°C and the residence time is 36 minutes. The total residence time is 120 minutes. , the width of the polyacrylonitrile-based precursor strand is controlled to be 72mm, and the electrostatic value of the polyacrylonitrile-based precursor strand is y=2.8, with the unit of V; the low-temperature carbonization process is carried out at 550°C in the presence of an inert gas, with a total draft ratio of 1.05 times; the high-temperature carbonization process is carried out at 1250°C in the presence of an inert gas, with a total draft ratio of 1.06 times; the graphitization process is carried out at 2350°C in the presence of an inert gas; the surface treatment adopts an electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 2%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The obtained carbon fiber has a tensile strength of 3.85GPa, a tensile modulus of 381GPa, and an interlaminar shear strength of the carbon fiber composite material of 38.4Mpa.
[0083] Comparative Example 3
[0084] The polyacrylonitrile-based precursor filament bundle (self-made, with 1000 strands in a single bundle and a fineness of 0.83dtex) is sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling, drying, and finally the high-strength and high-modulus carbon fiber is obtained. The pre-oxidation process is carried out in an air atmosphere, and passes through three temperature zones in sequence. The pre-oxidation temperature in the first temperature zone is 220°C and the residence time is 60min. The pre-oxidation time in the first temperature zone accounts for a percentage of x=50% of the total pre-oxidation time. During the pre-oxidation treatment in the first temperature zone, the drafting ratio of the polyacrylonitrile precursor is 1.0. The pre-oxidation temperature in the second temperature zone is 240°C and the residence time is 30min. The pre-oxidation temperature in the third temperature zone is 250°C and the residence time is 30min. The total residence time is 120min. During the pre-oxidation process in the first temperature zone, , the width of the polyacrylonitrile-based precursor strand is controlled to be 1mm, the electrostatic value of the polyacrylonitrile-based precursor strand is y=0.05, the unit is V; the low-temperature carbonization process is carried out at 650℃ in the presence of inert gas, and the total draft ratio is 1.05 times; the high-temperature carbonization process is carried out at 1400℃ in the presence of inert gas, and the total draft ratio is 1.06 times; the graphitization process is carried out at 2500℃ in the presence of inert gas; the surface treatment adopts the electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 2%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The obtained carbon fiber has a tensile strength of 3.74GPa, a tensile modulus of 381GPa, and an interlaminar shear strength of the carbon fiber composite material is 19.5Mpa.
[0085] Comparative Example 4
[0086] The polyacrylonitrile-based precursor filament bundle (self-made, with 320,000 strands in a single bundle and a fineness of 6.12 dtex) was sequentially subjected to pre-oxidation, low-temperature carbonization, high-temperature carbonization, graphitization, surface treatment, water washing, oiling, drying, and finally the high-strength and high-modulus carbon fiber was obtained. The pre-oxidation process is carried out in an air atmosphere and passes through three temperature zones in sequence. The pre-oxidation temperature in the first temperature zone is 220°C and the residence time is 72 minutes. The pre-oxidation time in the first temperature zone accounts for x=60% of the total pre-oxidation time. During the pre-oxidation treatment in the first temperature zone, the drafting ratio of the polyacrylonitrile precursor is 1.03. The pre-oxidation temperature in the second temperature zone is 235°C and the residence time is 20 minutes. The pre-oxidation temperature in the third temperature zone is 250°C and the residence time is 28 minutes. The total residence time is 120 minutes. During the pre-oxidation process in the first temperature zone, the pre-oxidation temperature is 250°C and the residence time is 28 minutes. The total residence time is 120 minutes. , the width of the polyacrylonitrile-based precursor strand is controlled to be 101mm, the electrostatic value of the polyacrylonitrile-based precursor strand is y=0.015, the unit is V; the low-temperature carbonization process is carried out at 800℃ in the presence of inert gas, and the total draft ratio is 1.05 times; the high-temperature carbonization process is carried out at 1550℃ in the presence of inert gas, and the total draft ratio is 1.06 times; the graphitization process is carried out at 2750℃ in the presence of inert gas; the surface treatment adopts the electrochemical pulse method, the electrolyte is ammonium bicarbonate, the electrolyte concentration is 2%, the electrolyte temperature is room temperature, and the surface treatment time is 60s. The obtained carbon fiber has a tensile strength of 4.08GPa, a tensile modulus of 467GPa, and an interlaminar shear strength of the carbon fiber composite material is 17.5Mpa.
[0087] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing high-strength and high-modulus carbon fiber, characterized in that: The method comprises pre-oxidizing polyacrylonitrile-based precursor fibers; Wherein, the pre-oxidation treatment is provided with at least three temperature zones, and in the first temperature zone, the ratio of the electrostatic value of the polyacrylonitrile-based precursor yarn to the width of the polyacrylonitrile-based precursor yarn is 0.005-0.032 V / mm.
2. The method according to claim 1, characterized in that: During the pre-oxidation treatment in the first temperature zone, the bundle width of the polyacrylonitrile-based precursor yarn is 0.0001-0.0008 times the number of strands in a single bundle of the polyacrylonitrile-based precursor yarn, and the bundle width of the polyacrylonitrile-based precursor yarn is measured in millimeters.
3. The method according to claim 1 or 2, characterized in that: In the first temperature zone, the electrostatic value y of the polyacrylonitrile-based precursor yarn satisfies the following formula: -1.3x 3 +2.4x 2 -0.65x+0.03<y<-3.4x 3 +6.5x 2 -0.12x+0.23; The unit of y is V, and x represents the percentage of the pre-oxidation time in the first temperature zone to the total pre-oxidation time, and the value range of x is 25%-85%.
4. The method according to any one of claims 1 to 3, characterized in that: During the pre-oxidation treatment, the width of the polyacrylonitrile-based precursor yarn is 4-80 mm.
5. The method according to claim 1, characterized in that The number of strands in a single bundle of polyacrylonitrile-based precursor fibers is 1,000-320,000.
6. The method according to claim 1, characterized in that The temperature in the first temperature zone is 200-270°C; Preferably, the pre-oxidation residence time in the first temperature zone is 20-100 min; Preferably, the stretching ratio in the first temperature zone is 1-1.
1.
7. The method according to any one of claims 1 to 6, characterized in that: The polyacrylonitrile-based precursor is prepared by a wet spinning process; Preferably, the fineness of the polyacrylonitrile-based precursor is 0.7-6 dtex.
8. The method according to claim 1, characterized in that The method further comprises: sequentially subjecting the oxidized fibers obtained by pre-oxidation to low-temperature carbonization treatment, high-temperature carbonization treatment, graphitization treatment, electrochemical treatment, water washing, sizing and drying.
9. The method according to claim 8, characterized in that The temperature of the low-temperature carbonization treatment is 400-800°C, and the total draft ratio is 0.95-1.08 times; Preferably, the temperature of the high temperature carbonization treatment is 1200-1600°C, and the total draft ratio is 0.97-1.08 times; Preferably, the temperature of the graphitization treatment is 2200-2800°C.
10. High-strength and high-modulus carbon fiber prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Surface treatment method and device for high-modulus carbon fibers and application of surface treatment method and device
CN109161947A
Large-tow carbon fiber surface treatment method and equipment
CN112709064A
Surface treatment method of dry-jet wet-spinning high-modulus carbon fibers
CN114086386A
Method for eliminating static electricity in carbon fiber production
CN104451962A
Preparation method of high strength electrospun polyacrylonitrile-based nanometer carbon fiber felt
CN108611793A